Reorientasi Strategi Pembangunan Ekonomi yang Berorientasi pada Rakyat - Edy Suandi Hamid (Universitas Islam Indonesia, 1999)
The discourse on people' economy in crisis and in the strong wave of reform movement is undoubtedly relevant. This is because of impact of the crisis on the people economy which is extremely huge. This article describes what so called the